2007
DOI: 10.1007/s11695-007-9200-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of size of proximal gastric pouch and short-term weight loss following routine upper gastrointestinal contrast study after laparoscopic Roux-en-Y gastric bypass

Abstract: Background: The authors investigated whether there is any correlation between gastric pouch size measured by routine upper gastrointestinal contrast study (UGI) after laparoscopic Roux-en-Y gastric bypass (LRYGBP) and short-term weight loss.Methods: The study group consisted of 82 patients (66F, 16M) who underwent LRYGBP. Body mass index before surgery ranged from 35.4 to 71.7 kg/m 2, with a mean of 47.4 kg/m 2. UGI was performed 1 day after LRYGBP in all patients. Proximal gastric pouch size was estimated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 13 publications
0
9
0
4
Order By: Relevance
“…Moreover, the small-sized gastric pouch is expected to contribute with a food intake restriction due to low reservoir capacity, and also due to low filling capacity, an increased wall tension in turn inducing signals of satiety or indigestion early during food intake. However, neither restriction at the gastrojejunostomy nor pouch size has been convincingly shown to be the point of action for reduced food intake and weight reduction following RYGBP [711]. It can be added that the surgical construction performed on the patients in the present study included a gastrojejunostomy with a diameter larger than 20 mm.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Moreover, the small-sized gastric pouch is expected to contribute with a food intake restriction due to low reservoir capacity, and also due to low filling capacity, an increased wall tension in turn inducing signals of satiety or indigestion early during food intake. However, neither restriction at the gastrojejunostomy nor pouch size has been convincingly shown to be the point of action for reduced food intake and weight reduction following RYGBP [711]. It can be added that the surgical construction performed on the patients in the present study included a gastrojejunostomy with a diameter larger than 20 mm.…”
Section: Discussionmentioning
confidence: 95%
“…The mechanisms behind the reduced caloric intake including optimized dietary preferences following RYGBP are still enigmatic despite recent findings on the role of gastrointestinal hormones [5, 6]. Furthermore, it remains controversial to what extent the size of the gastric pouch that is in continuity with the jejunal segment (the Roux limb), or restriction at the connecting stoma, influence food intake and subsequent weight reduction [711]. The Roux limb per se as a possible point of action for the successful outcome from RYGBP has been investigated very rarely.…”
Section: Introductionmentioning
confidence: 99%
“…Mason et al [5] reported that a large pouch size causes insufficient weight loss or weight regain and therefore suggested a pouch size of less than 50 ml. A negative correlation between pouch size and body weight loss after gastric bypass has also been described by Roberts et al [31], but this remains controversial [29,30]. The creation of a small gastric pouch in rats is technically demanding and a variety of different techniques has been described (table 1).…”
Section: Pouchmentioning
confidence: 87%
“…The gastric bypass operation in humans creates a small gastric pouch (20-50 ml) with very limited food storage capacity [29,30]. Mason et al [5] reported that a large pouch size causes insufficient weight loss or weight regain and therefore suggested a pouch size of less than 50 ml.…”
Section: Pouchmentioning
confidence: 99%
“…43 No correlation was found between the stomach pouch size and short-term weight loss following RYGB surgery when the proximal gastric pouch area was estimated by routine upper gastrointestinal contrast studies multiplying the maximal transverse by the longitudinal diameters. 44 Despite the significant weight loss of approximately 40% of the body weight at one year and dramatic improvement in obesity-related comorbidities following RYGB, some patients appear to experience suboptimal weight loss mitigating the improvement of comorbidities. 46 , 21 , 20 The reasons for suboptimal weight loss are not well understood, but the suboptimal weight loss is often ascribed to the patients' preoperative psychological characteristics or eating behaviors, as well as poor compliance with postoperative dietary and exercise recommendations.…”
Section: Weight Loss and Obesity-related Comorbidities Following Barimentioning
confidence: 99%